PENGEMBANGAN MEDIA PEMBELAJARAN NILAI – NILAI PANCASILA BERBASIS WEBSITE UNTUK SISWA KELAS V SD - Firah Amaliyah; Noviana, Eddy; Guslinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a website-based learning medium on Pancasila Values using Google Sites for fifth-grade students at SDN 183 Pekanbaru, as well as to determine the feasibility, practicality, and effectiveness of the developed medium. This study was motivated by the continued use of conventional learning media, which tends to make learning monotonous and less interactive. The research method used was Research and Development (R&D) employing the ADDIE model, limited to the development stage. The research subjects consisted of 3 students and 4 teachers in the one-to-one pilot test and 11 students in the small-group pilot test. The learning media included Pancasila values content, contextual videos, interactive quizzes based on Wordwall, and learning assessments. Expert validation results indicate that the media falls into the “highly feasible” category, with a 87.5% rating from design experts, 89.6% from content experts, and 87.5% from language experts. The one-on-one pilot test yielded a 95% rating in the “highly practical” category, while the small-group pilot test achieved a 93.86% rating in the “highly practical” category. The N-gain calculation result of 0.65 indicates that the media is quite effective in improving student learning outcomes. Thus, the website-based learning media using Google Sites is deemed highly suitable, highly practical, and quite effective for use in fifth-grade elementary school instruction.